Censorship detected in LY (Libya) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Libya. Data sourced from OONI.
Censorship Incident ID: LY-2026-0780. Severity: critical. Confidence: 90%